OPTIMALISASI DESA WISATA KELING KABUPATEN KEDIRI DENGAN PENDEKATAN COMMUNITY BASED TOURISM (CBT) - Nike Nur Latifah; Kalvin Edo Wahyudi (Halu Oleo University, 2025)
This study aims to determine the application of Community-Based Tourism in the development of Keling Tourism Village in Keling Village, Kepung District, Kediri Regency. This study uses a descriptive qualitative approach. Community-based Tourism is expected to play a significant role in the growth of Keling Tourism Village in Keling Village, Kepung District, Kediri Regency, and this study will provide a comprehensive picture of its application in this context. The results of this study found that the planning stages of the development of Keling Tourism Village had not involved all communities. At the implementation stage of development, there was a clear division between the village government and the community. The support from the BPD institution in the implementation stage established good communication between managers. The presence of Keling Tourism Village has more or less had an impact on the surrounding community, both in terms of economy and socio-culture. However, the implementation of CBT in Keling Tourism Village has been implemented quite well, but not optimally